Evaluation of mechanical probes used on uncooked steaks to classify beef longissimus tenderness - J.W. Stephens; Melvin C. Hunt; T.E. Lawrence; T.M. Loughin; John A. Unruh; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2003)
We pooled the mechanical probe data from two experiments to develop regression equations to predict beef longissimus tenderness. Fifty-three USDA Select strip loins were evaluated at 2 days postmortem with three mechanical probes to predict trained sensory panel (TSP) tenderness and Warner-Bratzler shear force (WBSF) of cooked steaks aged 14 days. The sharp needle, sharp blade, and plumb bob probes were correlated to TSP tenderness (r=-0.51, -0.45, and -0.35, respectively)and WBSF (r=0.56, 0.53, and 0.36, respectively). Regression equations developed from sharp needle, sharp blade, and plumb bob probe measurements and L* (lightness) values accounted for 49, 50, and 47% of the variation in TSP tenderness. The predicted values of equations were also used to classify the strips as tough or tender, and this classification was compared to the actual TSP tenderness classification. Of the steaks predicted to be tender by the equations using the sharp needle, sharp blade, and plumb bob probes and WBSF 88, 88, 84, and 87%, respectively, were actually tender according to TSP. The sharp needle, sharp blade, and plumb bob probe prediction equations were comparable to WBSF in classifying carcasses into sensory panel determined tenderness groups, and they were superior to WBSF in simplicity and cost.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Uncooked steaks; Longissimus tenderness